Directive-Following Based on Graphic Symbol Sentences Involving an Animated Verb Symbol: An Exploratory Study. (May 2022) - Choe, Nicole; Shane, Howard; Schlosser, Ralf W.; Haynes, Charles W.; Allen, Anna
Many children with autism spectrum disorder (ASD) demonstrate poor comprehension of language at the sentence level in both the spoken modality and the graphic symbol modality. This study explored whether children with ASD are able to follow directives when presented with a graphic symbol sentence that includes an animated symbol for a verb. A total of five participants with moderate-to-severe ASD were presented with 10 graphic symbol sentences and asked to perform the directive using the provided figurines/objects. Results demonstrated that children with ASD can correctly carry out full-sentence directives to varying degrees when the directives represented graphically include an animated verb. Several observations were noted pertaining to participants' performance and autism severity. The results of this study may have important implications for using animation as a tool to facilitate symbol syntax comprehension.